Patient Experience Diagnosis: Using Telemed Simulation to Assess Health Care Provider Verbal and Nonverbal Communication Issues to Prescribe Potential Interventions - Guan, Xiaowen; Porter, Mike C.; Omodt, Paul G. (Patient experience journal, 2024)
Patient experience contributes to health outcomes, and a host of healthcare organization success factors, including profitability. Often applied and academic analysis of patient experience applies macro-level approaches to defining issues and suggesting improvements. Guided by the theoretical framework of provider-patient communication during telemedicine, this study used a simulation to measure impacts of provider behaviors that might be improved through communication training to positively impact outcomes on both sides of patient care. The study employed between-subject experimental design to investigate impacts of provider verbal and nonverbal communication on patient satisfaction during telemedicine consultations. Participants, randomly assigned to one of eight experimental conditions, watched a recorded telemedicine “consultation” with either a male or female provider that displayed either high- or low-immediacy nonverbal cues. Participants imagined being the patient and completed a survey regarding perceptions of provider communication and evaluation of the experience. Results suggest a healthcare provider’s verbal and nonverbal communication represents a significant predictor of patient satisfaction, even during telemedicine. The findings provide empirical evidence for Miller’s model and point to the importance and potential of improving providers’ verbal and nonverbal communication skills through communication training on specific interpersonal skills.